Przesłanki prawomocności decyzji interpretacyjnych w teorii wykładni Jerzego Wróblewskiego - Pulka, Zbigniew (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
In the article the Author carries on his deliberations on the metatheoretical level. He aims at answering the question: what is the cognitive status of the Jerzy Wróblewski’s theory of interpretation?By cognitive status the Author means descriptive or normative character of the theoretical propositions about interpretation, as well as premises of validity of these propositions. The Author focuses on reasons why these propositions are accepted. He discusses such reasons as: correspondence between these propositions and some interpretative reality, as well as primary acceptance of definite axiological premises. The Author especially strives to answer the question of great epistemological importance: is it true, that logical corollaries of philosophical propositions inevitably turn out to be philosophical statements? Trying to answer this question, the Author especially takes into account the premises of validity of interpretative decision which are assumed by Jerzy Wróblewski’s theory of interpretation.
Keywords: Wróblewski, Jerzy (1926-1990); theory of interpretation; premises; validity